2013
DOI: 10.4103/0028-3886.107942
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing residual or recurrent cerebral aneurysms after clipping by computed tomographic angiography: Meta-analysis

Abstract: As a noninvasive and convenient screening method, CTA has a high diagnostic value for the detection of the residual or recurrent aneurysms after clipping. In the future, it may be used as a routine diagnostic tool for evaluation of aneurysms after clipping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…CT angiography (CTA) is a convenient, noninvasive and reliable method for evaluation before treatment and after coiling or clipping treatment. 1,2 When metal coils or clips are placed in the cerebral artery, artefacts from metals may be produced, which usually influences the post-operative evaluation, especially the detection of residual aneurysm. Digital subtraction angiography is invasive and expensive even though it is the gold standard for diagnosis of the vascular diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CT angiography (CTA) is a convenient, noninvasive and reliable method for evaluation before treatment and after coiling or clipping treatment. 1,2 When metal coils or clips are placed in the cerebral artery, artefacts from metals may be produced, which usually influences the post-operative evaluation, especially the detection of residual aneurysm. Digital subtraction angiography is invasive and expensive even though it is the gold standard for diagnosis of the vascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…15 The application of CTA in cerebral aneurysms has been reported in several studies. 2,8 There are some reports on improving image quality and reducing artefacts by spectral CT. However, as far as we know, the effect of artefact reduction from metal coils or clips by using GSI in patients with cerebral aneurysms has not been described in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies suggest that postoperative assessment of clipped aneurysms can be performed with CTA, as an alternative for DSA [7, 8, 12], or suggest to limit the use of DSA to certain indications [10, 17, 27]. However, a recent meta-analysis, with a total of 487 aneurysms, showed that CTA had a pooled sensitivity of only 71% and specificity of 94% for identifying residual or recurrent aneurysms in comparison to DSA [25]. For aneurysm residuals < 2 mm, the sensitivity has been shown to be even lower [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, performing DSA routinely adds risk [29] and burden to a majority of patients whose aneurysms prove to be adequately obliterated. A less invasive alternative is computerized tomographic angiography (CTA), but this imaging technique has been shown to be less sensitive [25]. With the number of reoperations being small [5], no consensus currently exists regarding the implementation of routine postoperative imaging, either DSA or CTA.…”
Section: Introductionmentioning
confidence: 99%
“…In a meta-analysis of 10 studies, the pooled sensitivity and specificity for detecting residual or recurrent aneurysms after clipping were 71% and 94%, respectively. CTA appears to be limited in detecting aneurysms less than 3 mm or when multiple clips were used [11]. Accuracy is also improved with the use of titanium clips and a multi-slice detector CTA [11][12].…”
Section: Discussionmentioning
confidence: 99%